IMPROVING THE STUDENTSâ€™ UNDERSTANDING VOCABULARY MEANING OF DESCRIPTIVE TEXTS THROUGH CONTEXT CLUES STRATEGY - Apriliyanti, Mira; Arifin, Zainal; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This research aimed to improve the students understanding vocabulary meaning of a descriptive text through context clues strategy to the eighth-grade students of MTs Negeri 1 Pontianak. The research was a classroom action research that comprised of planning, acting, observing, and reflecting. This study had three cycles. The subjects of the research were VIII E, with 42 students. The researchers used observation and measurement tests to collect the data. The tools were an observation checklist, field note, and a vocabulary test. The result showed that Context clues strategy had improved students understanding vocabulary meaning, in adjectives vocabulary in the descriptive text. The clues were useful in helping the students to guess the meaning of unfamiliar words. (1) For the synonym the student had to pay attention to the word â€œalsoâ€, â€œandâ€, â€œorâ€, and â€œcommasâ€. (2) Antonym, â€œbutâ€, â€œhoweverâ€, â€œorâ€, and â€œcommasâ€. (3) Definition, â€œmeansâ€, â€œthat isâ€, â€œsemicolonâ€, â€œfull stopâ€ or â€œparenthesesâ€. (4)Explanation, â€œsuch asâ€ and â€œthe exampleâ€. By then, the students could find themeaning of the word easily it ultimately makes the achievement improved significantly. In conclusion, teaching vocabulary meaning by using context clues strategy successfully improved the studentsâ€™ understanding of the vocabulary meaning of the descriptive text.Keywords: Context Clues Strategy, Vocabulary Meaning, Descriptive Text,Classroom Action ResearchÂ